A psycho-oncological approach to addressing cancer disparities in Nigeria (2012)
We describe the formation of a specialized, international research partnership between two university communities: the University College Hospital (UCH), University of Ibadan, Nigeria, and the Albert Einstein College of Medicine (Einstein) of Yeshiva University, Bronx, New York, USA. Our partnership is focused on cancer. It seeks to establish a platform for a wide variety of prevention and control activities, including cancer surveillance, community outreach and education, screening and diagnosis, treatment and post-treatment (survivorship), as well as palliation. Our approach is grounded by principles of psycho-oncology, an emerging sub-discipline of research and clinical intervention in cancer, and uses psycho-social and behavioral research as a means to build ‘collaborative capacity’ and to prioritize and manage resources for patients, families and health care professionals.